AB0175 Dysregulation of nf-Κb in glandular epithelial cells results in sjÖgren's-like features. (12th June 2018) - Wang, X.; Shalaan, A.; Liefers, S.; Proctor, G.; Bootsma, H.; Kroese, F.; Pringle, S.
Abstract : Background: Hyposalivation and lymphocytic infiltration in salivary glands are common manifestations of primary Sjögren's syndrome [1] . NF-kappa B (NFκB) signalling is one of the most important proinflammatory pathways, and is inhibited by A20 (also known as TNFAIP3) [2] . Although mounting studies are pointing to the central role of epithelial cells in pSS [3–5], whether pSS-like features can be initiated by immune activation of epitheliums remains to be explored. Objectives: We sought to investigate the hypothesis that epithelial cells are capable of initiating the major pathological salivary gland hallmarks of primary Sjögren's syndrome. In order to achieve this we employ a keratin 14 (KRT14) promoter-driven knockout of the A20 NFκB signalling inhibitor. Methods: A20 gene expression was knocked out in KRT14 + cells, namely ductal and myoepithelial cells. Whole pilocarpine-stimulated saliva was collected from A20 -/- mice and wildtype (WT) littermate controls at 10, 20 and 30 weeks of age. Submandibular SGs were harvested at all time points for histological examination and qPCR. Results: In submandibular SGs of A20 -/- mice at 30 weeks of age, 10% of all cells were CD45 + leukocytes and 3% were CD3 + T cells, both significantly more than controls. B cell proportion increased over time in A20 -/- mice, but was not significantly different to controls. CD45 + cells formed immune foci (>50 CD45 + cells together) localised to striated ducts, present at significanty greater frequencies than control mice. CD45 + cells, T cells and occasional B cells in A20 -/- mice also invaded striated ducts. Expression of the pro-inflammatory cyto/chemo-kines IFNγ, TNFα, IL-6, CXCL10 and CXCL13 was also significantly greater in A20 -/- mice. Functionally, both volume and mucin 10 content of whole stimulated saliva from A20 -/- mice was significantly reduced compared to controls. Conclusions: We present a model for epithelial cell involvement in pSS SG pathology development. We confirm that saliva production defects, foci formation and striated duct invasion can be triggered solely by immune activated epithelial cells. References: [1] Brito-Zerón P, et al. Early diagnosis of primary Sjögren's syndrome: EULAR-SS task force clinical recommendations. Expert Rev. Clin. Immunol. 2016;12:137–156. [2] Shembade N, Ma A, Harhaj EW. Inhibition of NF-kappaB signaling by A20 through disruption of ubiquitin enzyme complexes. Science2010;327:1135–9. [3] Spachidou MP, et al. Expression of functional Toll-like receptors by salivary gland epithelial cells: increased mRNA expression in cells derived from patients with primary Sjögren's syndrome. doi:10.1111/j.1365-2249.2006.03311.x [4] Ittah M, et al. B cell-activating factor of the tumor necrosis factor family (BAFF) is expressed under stimulation by interferon in salivary gland epithelial cells in primary Sjögren's syndrome. Arthritis Res. Ther. 2006;8:R51. [5] Fox RI, Kang HI, Ando D, Abrams J, Pisa E. Cytokine mRNA expression in salivary gland biopsies of Sjögren's syndrome. J. Immunol1994;152:5532–9. Disclosure of Interest: None declared